SOCIAL NETWORK ANALYSIS OF TADOM HILL, BANTING, SELANGOR AND THE IMPLICATIONS UPON IT’S MANAGEMENT - Siti Mariam Mellisa Abdullah; Nurhidayah Zakaria; Fatin Farazh Ya’acob; Mohd Shahwahid Haji Othman (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Purpose - Community-based management practice is set as an illustration of how local stakeholders participation many problems and dilemmas in connection with governing ecotourism could be better resolved. A case study of Tadom Hill (TH) in Banting, Selangor has been facing complaints from the local indigenous community concerning the governance of the resort. The aim of this study to identify the stakeholders, their roles in the social network of TH, characterize their relationships between them and establish the effects on governance issues at TH. Design- A survey was administrated to different groups of stakeholders who has connection with TH in order to characterize the relationships between them and establish their effects on governance issues at TH. Methodology - Social Network Analysis (SNA) method was used to identifies the key stakeholders and their roles in the social network of TH. Findings - The results gained from the SNA has provided greater thorough information of the top-down management approach at the resort. For a resort to be efficiently managed, effective involvement of the stakeholders is essential. Conclusion - It was concluded that the management of the ecotourism services at TH need the involvement of local stakeholders in the pursuit of greater co-management at the resort.